PENINGKATAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SNOWBALL THROWING PADA MATA PELAJARAN IPS DI KELAS V SD - Masta Ginting (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2016)
ABSTRACTThis study aims to determine the material improvement of learning outcomes of socialscience subject with the topic Dutch colonization in Indonesia. This study is a classroomaction research (CAR). The subjects were fifth grade students totaling 28 students. Thetechnique of data analysis in this study is a qualitative description. On the pretest,students who completed 5 people with a percentage of 17.86%, which did notcomplete as many as 23 people with a percentage of 82.14% and the average score of48.11. In cycle I students who pass as many as 10 people with a percentage of 35.71%,which did not complete as many as 18 people with a percentage of 64.29% and theaverage value of 50.49. In the second cycle complete as many as 24 people with apercentage of 85.71% and students who did not complete as many as four people witha percentage of 14.29% and the average score 81.20 level in the classical completenesssecond cycle is 85.71%.Keywords: Snowball Throwing, Learning Outcomes, Social ScienceABSTRAKPenelitian ini bertujuan untuk mengetahui peningkatan hasil belajar IPS materipenjajahan belanda di indonesia. Jenis penelitian ini adalah penelitian tindakan kelas(PTK). Subjek penelitian adalah siswa kelas V yang berjumlah 28 siswa. Adapun teknikanalisis data dalam penelitian ini adalah deskripsi kualitatif. Pada pretest, siswa yangtuntas sebanyak 5 orang dengan persentase 17,86 %, yang tidak tuntas sebanyak 23orang dengan persentase 82,14 % dan nilai rata-ratanya sebesar 48,11. Pada sikulusI siswa yang tuntas sebanyak 10 orang dengan persentase 35,71 %, yang tidak tuntassebanyak 18 orang dengan persentase 64,29 % dan nilai rata-ratanya 50,49. Padasiklus II tuntas sebanyak 24 orang dengan persentase 85,71 % dan siswa yang tidaktuntas sebanyak 4 orang dengan persentase 14,29 % dan nilai rata-ratanya 81,20tingkat ketuntasan secara klasikal siklus II adalah 85,71 % .Kata Kunci : Snowball Throwing, Hasil Belajar, IPS